Формирование выходного напряжения многоуровневого инвертора на базе ортогональных преобразований - Терещенко, Т.А.; Беженар, В.А. (Технічна електродинаміка, 2012)
An algorithm is proposed for the forming of multilevel inverter output voltage based on orthogonal transforms - Walsh, Hartley, transform at oriented basis (OB) and extended OB-transform. The advantages and disadvantages of obtained multilevel inverter schemes are evaluated from the point of switching frequency and total harmonic distortion.